An application of analogues of two-sided Kurpel’s methods to ordinary differential equations - Kopach, M.I.; Obshta, A.F.; Shuvar, B.A. (Carpathian Mathematical Publications, 2010)
An analogues of two-sided Kurpel's methods of approximate solution of ordinary differential equation that give possibility to get above-linear convergence in the case of nondifferential right part are constructed and investigated.